Understanding Non-Hodgkin Lymphoma – A Growing Challenge in Cancer Care - Mumtaz, Sami Ullah (Pakistan Journal of Health Sciences, 2024)
Non-Hodgkin lymphoma is a type of blood cancer that originates in the lymphatic system a system very crucial for immune function. Unlike Hodgkin's Lymphoma, NHL is a group of cancers progressing at different rates, ranging from slow to fast. It originates in the lymphatic system making the diagnosis and treatment of this cancer particularly challenging, as each subtype requires a different approach. There rate of NHL has been increasing in recent years, and while the exact cause of this increasing number is still not clear there are factors that are contributing such as environmental influences, lifestyle changes, and an aging population. NHL affects people of all ages, but it is most commonly diagnosed in individuals ages 60 or older. One of the major issues in managing NHL is the symptoms that seem subtle, and are often mistaken for less serious conditions. Swollen lymph nodes, fever, night sweats, and unexplained weight loss are common signs of NHL but they can be attributed to other illnesses. As a result NHL is often diagnosed late which delays treatment and reduces the chances of successful outcomes. Recent advances in the treatment of NHL are promising. For fast-growing or the aggressive type chemotherapy remains the standard treatment, but some new therapies are making successful strides. Some therapies only focus on the cancerous cells and there is little damage done to the healthy tissues unlike chemotherapy which has proves to be more effective and less toxic Patients with refractory or relapsed NHL can be treated with immunotherapy which is the use of monoclonal antibodies and CAR T- cell therapy, strengthening the immune system to fight cancer more efficiently. The progress in the treatment of NHL is encouraging however early detection of it could be beneficial. There is imperative need for increased awareness of NHL symptoms. Research into the molecular and genetic underpinnings of NHL is also crucial for developing more precise treatments tailored to individual patients. A holistic approach is essential that addressing not just the physical needs but also the emotional needs of the patients. As healthcare providers, such as the oncologists, hematologists and pathologists collaborate their combined efforts can help improve survival rates as well as the quality of life. In conclusion, while the challenges of Non-Hodgkin lymphoma remain, advances in treatment, early detection, and patient care bring renewed optimism for those battling the disease.